THE PACIFYING POLICE UNITS IN RIO DE JANEIRO: a bypass of what? - Machado, Marta Rodriguez de Assis (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
In their book, Prado and Trebilcock analyze the Pacifying Police Units (UPPs) as a case of intentional bypass (2018, 63-76). On the one hand, the bypass hypothesis addresses the hurdles of reforming the public security system and the police’s chronic problems of corruption, institutional racism, and violence; on the other, it brings the design of a “new model,” with a different rationale and a separate institutional structure. According to the authors, the creation of a new police unit (the UPPs) – independent from the regular police force, with special training and new recruits –indicates an institutional design that makes the UPPs a case of bypass.